Produção de mudas de Salvia splendens e Pachyveria glauca em substratos de biocarvão de lodo de esgoto e casca de arroz - Lorrane Aguiar Rodrigues (2017)
The production of sewage sludge, a byproduct of sanitation services, tends to increase gradually as a result of increased urbanization and population growth. Several procedures have been adopted for disposal: disposal in landfills, incineration, landfarming, application in agriculture and in forest plantations. The increase in sludge generation, as well as the difficulties encountered for its final destination, has motivated the research focused on the development of technologies that promote the correct use of this residue. Among these, great attention has been given to the pyrolysis of sludge, with a view to converting it into added-value by-products. Biochar, a byproduct of pyrolysis, has the potential to provide benefits such as carbon storage and improved soil properties, which can minimize the negative environmental impacts resulting from the final disposal of biomass residues, giving a noble end to the waste through its reinsertion into the environment. One of the ways of using biochar is as a substrate for the production of various seedlings, due to its beneficial characteristics like slow release of nutrients and improvement of their physical properties. Within horticulture, one of the segments that has been expanding lately is floriculture, due to its profitability. In this sector, there is great demand for the use of agricultural substrates. The use of substrates for the production of seedlings is of great importance, since the quality of seedling also depends on the substrate used in its cultivation. The application of biochar in the production of ornamental plant seedlings has advantages over agricultural crops, since the products from these plants are not edible, minimizing the risks of contamination of man, appearing as a promising alternative for the management of this residue. Still, ornamental plants stand out for their beauty, being highly valued in the national and international market. The objective of this work was: 1) to produce biochar (BC) from sewage sludge (LE) and rice husk (CA); 2) to evaluate the growth and development of saplings of Salvia splendens and Pachyveria glauca on substrates composed of increasing doses of biochar. The treatments corresponded to the biochar in the following proportions: 0% LE + 100% CA; 20% LE + 80% CA; 40% LE + 60% CA; 60% LE + 40% CA; 80% LE + 20% CA; And 100% LE + 0% CA, and a control treatment consisting of Bioplant® commercial substrate. The statistical design of the experiment was in randomized blocks, totaling 7 treatments and 4 replicates. The following results were obtained: 1) the different proportions of LE and CA in the substrates did not influence the emergence speed and the percentage of emerged seeds of Salvia splendens; 2) the proportions of LE and CA between 20-80% provided plants with a quality equal to or higher than the commercial substrate, with respect to plant height and diameter, inflorescence length and number of flowers; 3) substrates composed of biochar only from LE or CA are not the most suitable for seedling production; 4) the use of BCCA only or the use of BCLE doses up to 20% of the substrate favors faster sprouting of Pachyveria glauca cuttings; 5) BCCA + BCLE mixtures provided a suitable culture medium for the production of Pachyveria glauca seedlings, since it produced seedlings with biometric characteristics equivalent to the control treatment and with ornamental appearance suitable for commercialization; 6) the conversion of LE into biochar for use as an agricultural substrate proves to be a promising alternative for the environmentally correct disposal of the residue.